Improving Discharge Instructions Following a Concussion Diagnosis in the Pediatric Emergency Department: A Pre-post Intervention Study. Issue 5 (26th September 2021) - Yengo-Kahn, Aaron M.; Hibshman, Natalie; Bezzerides, Michael; Feldman, Michael J.; Vukovic, Adam A.; Mummareddy, Nishit; Zhao, Shilin; Penrod, Cody H.; Bonfield, Christopher M.; Vance, E. Haley
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Many children are discharged from the pediatric emergency department (PED) with incomplete or inappropriate instructions following a concussion. Our objective was to evaluate the effectiveness of a simple intervention in improving discharge instruction disbursement and completeness following PED diagnosis of concussion. Methods: A pre/post intervention study of 935 patients (375 preintervention and 560 postintervention) ages 5–19, diagnosed with a concussion and discharged from the PED between July 2016 and November 2019, was performed at a single United States pediatric tertiary-care center. Dedicated provider education sessions were held, and a consensus guideline–based set of discharge instructions were implemented in the electronic health record. Primary outcomes included the presence of return-to-play (RTP) instructions, return-to-learn (RTL) instructions, follow-up recommendations, and "complete" discharge (ie, all 3 components present). Statistical process control charts were generated and tested for special cause variation. Results: More patients received instructions for RTP (87% versus 59%) and RTL (60% versus 3%), and a complete discharge was more frequent (45% versus 2%), following the conclusion of the intervention. Only the improvement in RTP instructions was completely sustained into the following academic year, whereas RTL and complete discharge rates declined to 27% and 20%, respectively. Conclusions: A simple, low-cost intervention such as peer-to-peer education and consensus guideline–based discharge instruction templates can significantly improve discharge readiness after pediatric concussion. Further work is needed to maintain progress and continue improvements, at our large academic trauma center.